Pengaruh Perubahan Suhu terhadap Panjang Standar dan Kelangsungan Hidup Nauplius Udang Vaname (Litopenaeus vannamei) - Aulya Anjelyna; Achmad Kusyairi; Sri Oetami Madyowati (Zebra: Jurnal Ilmu Peternakan dan Ilmu Hewani, 2026)
Whiteleg shrimp (Litopenaeus vannamei) is a leading commodity in aquaculture in Indonesia due to a number of advantages such as disease resistance, rapid growth, high survival rate, and feed conversion efficiency. Whiteleg shrimp contributes significantly to Indonesian fisheries exports, reaching 38.98% in 2021. To meet high market demand, increasing the productivity and quality of whiteleg shrimp is very important, where the quality of the shrimp is influenced by the quality of the fry. Good management, including selecting quality broodstock, proper handling of eggs and nauplii, and maintaining optimal water quality, is very important in producing quality whiteleg shrimp fry. This study aims to determine the effect of temperature on the growth length and life expectancy of whiteleg shrimp nauplii. The study was conducted using a completely randomized design with three different temperature treatments (26°C, 29°C, and 32°C). The whiteleg shrimp nauplii used had an average size of 328.24mm obtained from PT. Delta Windu Purnama Situbondo. The water quality parameters used are Temperature, pH, salinity, and DO. Delta Windu Purnama Situbondo. Data were analyzed using SPSS 16.